THE RELATIONSHIP BETWEEN NURSING TECHNICIANS' EMOTIONAL LABOR AND THEIR PSYCHOLOGICAL WELL-BEING IN SAUDI CRITICAL CARE UNITS - Hazza Affat Matir Al-Dhafeeri, Faiz Affat Matir Al-Dhafeeri, Yousef Salama Saeed Al-Dhafeeri, Sultan Harbid Shaewan Al-Dhafeeri, Amal Furaih Alshammari, Monefa Fuoreh Saud Alshamry, Salfah Ali Sorur Almutiri, Mishean Faraj Alharbii (Chelonian Research Foundation, 2022)
Nursing technicians in critical care units often engage in emotional labor, which involves managing their emotions to meet the demands of their job. This study aims to investigate the relationship between nursing technicians' emotional labor and their psychological well-being in Saudi critical care units. A cross-sectional survey design will be used to collect data from a sample of nursing technicians working in critical care units of hospitals in Saudi Arabia. The Emotional Labor Scale and the Ryff's Psychological Well-Being Scale will be used to measure the variables. Descriptive and inferential statistics will be employed to analyze the data. The findings of this study will provide insights into the impact of emotional labor on nursing technicians' psychological well-being and inform strategies to support their mental health in the workplace.